Exploring the pharmacological potential of Moringa oleifera folium in health applications: A review - Kadek Rahayu Darma Yanti; Wirawati, Kadek Tania; Ompusunggu, Gabrios Bonauli; Wardani, Luh (Pharmacy Reports, 2024)
This review synthesizes current knowledge on the therapeutical potential of Moringa oleifera leaf extract in health. M. oleifera has transitioned from traditional medicine to the forefront of scientific investigation due to its exceptional phytochemical diversity and pharmacological versatility. Evidence supporting cardiovascular, metabolic, and renal benefits is assessed, highlighting mechanisms including nitric oxide modulation, anti-adipogenic effects, protein glycation inhibition, and renoprotection in diabetic conditions. The anti-inflammatory properties of M. oleifera are examined across gastrointestinal, neurological, and pulmonary systems, with significant findings in inflammatory bowel disease models, microglial enzyme modulation, and cancer suppression. Recent research on specific bioactive fractions, molecular targets, and signaling pathways provides mechanistic insights into M. oleifera's therapeutic actions. While substantial preclinical evidence supports M. oleifera's potential, it identifies critical research gaps, particularly in clinical validation, standardization, and pharmacokinetics. M. oleifera represents a promising sustainable resource for addressing global health challenges, especially in chronic disease prevention and management.